Study on Reasonable Energy Supplement Time of Tight Sandstone Oil Reservoirs with Rock Compressibility Stress Sensitivity - Tian Xiaofeng; Tan Xianhong; Tian Ji; Li Nan; Yuan Zhongchao; Liang Bin (Geofluids)
A-HBR field is a tight sandstone oil reservoir with a threshold pressure gradient and a rock compressibility stress sensitivity. However, no existing approach could predict reasonable energy supplement time considering both of them. Therefore, in this paper, rock compressibility stress sensitivity experiments are conducted. Then, a new approach is presented. This approach considers the correlation of rock compressibility and formation pressure. And the formation pressure is different from the development time and distance to oil well. The study suggests that the energy supplement time is later when the original rock compressibility is larger. The energy supplement time is earlier when the rock compressibility is more severe. A-HBR field’s reasonable energy supplement time is 83 days when considering the effect of rock compressibility stress sensitivity. It is much earlier than that when not considering the effect of rock compressibility stress sensitivity.